BRIEF CONSIDERATIONS REGARDING THE PROPERTY TRANSFERRING OR ENGENDERING OF OBLIGATIONS CHARACTER OF THE SALES CONTRACT - Vlad-Victor OCHEA (Challenges of the Knowledge Society)
I herein want to emphasize the main aspects regarding the property/real estate transferring or engendering of obligations character of the sales contract governed by the Romanian Civil Code of 2009.